Staphylococcus aureus Vaccine Research and Development: The Past, Present and Future, Including Novel Therapeutic Strategies - Clegg, Jonah; Soldaini, Elisabetta; McLoughlin, Rachel M.; Rittenhouse, Stephen; Bagnoli, Fabio; Phogat, Sanjay (Frontiers in Immunology, 2021)
Staphylococcus aureus is one of the most important human pathogens worldwide. Its high antibiotic resistance profile reinforces the need for new interventions like vaccines in addition to new antibiotics. Vaccine development efforts against S. aureus have failed so far however, the findings from these human clinical and non-clinical studies provide potential insight for such failures. Currently, research is focusing on identifying novel vaccine formulations able to elicit potent humoral and cellular immune responses. Translational science studies are attempting to discover correlates of protection using animal models as well as in vitro and ex vivo models assessing efficacy of vaccine candidates. Several new vaccine candidates are being tested in human clinical trials in a variety of target populations. In addition to vaccines, bacteriophages, monoclonal antibodies, centyrins and new classes of antibiotics are being developed. Some of these have been tested in humans with encouraging results. The complexity of the diseases and the range of the target populations affected by this pathogen will require a multipronged approach using different interventions, which will be discussed in this review.